Trendstudie 2018: Lese- und Schreibverhalten der Generationen X, Y, Z - Julia Hilgers-Sekowsky; Cansu Oral; Gabriele Schuster (IUBH Internationale Hochschule, 2018)
– This paper describes an integrated research study project developed and conducted with Dual program students of the IUBH University of Applied Sciences in Berlin, Düsseldorf and Hamburg. The project investigates the current reading and writing behavior of generations X, Y and Z. In addition, the study investigates the interest in and the acceptance of books, E-Book writing and publishing within these generations. This is an interesting research context as the amount of readers in the younger generation has been declining in the past years. The study analyzes the needs of the generations regarding their media usages, their attitude towards reading and writing and their knowledge about self-publishing. The results from this study allow for recommendations for online and offline publishing as well as social writing platforms and self-publishing companies. For instance, it shows that Generation X is the main consumer of E-books. Further, Generation Z will be an attractive newly evolving target group for paper books. The willingness to pay for traditional paper books differs within the generations. Therefore, it might be valuable to consider customized pricing strategies for the different generations (i.e. children's special rebates). Book recommendations through media and newsletters reach generations Y and Z, the customers of the future. Companies could employ content marketing through social media in order to reach these customers. Due to the different interests of the generations, we propose a differentiated targeting strategy. Available information on the self-publishing market is rather scarce so that potential consumers of these services are not fully aware of the publishing process . The area is relatively unknown within both the wider public and researchers. For this reason , this study contributes both to research and to practice by offering an approach on how to reach potential consumers of self-publishing services effectively .
Keywords: A1; A2; A13; A22; M3; M30; M31; M37; 650; Generation X; Generation Y; Generation Z; Lesen; Schreiben; Publizieren; Verlegen; Self-Publishing; E-Books; Bücher; Trends